An evaluatıion of oral health status in children with down syndrome according to socio-economic and educational status of their families - Ünal, Elif Mutlu (My University, 2019)
Amaç: Bu çalışma; Down Sendromlu çocuklarda ağız sağlığı durumunu, ailelerinin sosyo- ekonomik ve eğitim düzeylerine göre incelemeyi amaçlamaktadır. Bu araştırma da; yüksek sosyo-ekonomik ve eğitim düzeyine sahip Down Sendromlu çocuk sahibi aileler ile düşük sosyo-ekonomik ve eğitim düzeyine sahip Down Sendromlu çocuk sahibi aileleri karşılaştırarak, aradaki farkları belirlemeyi amaçlamaktadır. Gereç ve Yöntem: Araştırma cross-sectional özellik göstermektedir. İkameti İstanbul’da bulunan ve Marmara Üniversitesi hastası olan 66 Down Sendromlu çocuk, ağız sağlığı ve ailelerin sosyo-ekonomik ve eğitim düzeyi açısıyla hem anket hem de klinik muayene ile velileri tarafından sözlü olarak anamnez alınarak değerlendirilmiştir. Bulgular: Cinsiyet grupları arasında; Chi kare testi ile diş fırçalama sıklığı, ebeveynlerin bilinci, ağız muayenesi sıklığı, medikal tedavi alma ve tedavi sırasında stres yaşama, eğitim düzeyi gibi kategoriler incelenmiştir. Aile farkındalığı listesinde 3 grup arasında; Diş fırçalama sıklığı, medikal tedavi, gelir ve eğitim düzeyi, tedavi sırasındaki stres ve oral kontrol sıklığı gibi kategoriler Chi kare testi ile karşılaştırıldı. Tüm analizlerde anlamlılık düzeyi 0.05 olarak ölçüldü ve doğruluğu kanıtlanmıştır. Sonuçlar: Down sendromlu çocukların ailelerinin sosyoekonomik düzeyi, ağız sağlığı durumlarında ve düzeylerinde önemli rol oynamaktadır.

Aim: The aim of this study is to examine the oral health status of children with Down syndrome in terms of the socio-economic and educational levels of their families. In this study a comparison has been made between families with a high socio-economic and educational level of children with offspring with Down’s syndrome and families with low socio-economic and educational level with Down's syndrome to determine the differences. Material and Method: The study is cross-sectional. 66 children with Down Syndrome that are patients of Marmara University, have been assessed for oral health with a clinical examination and their families have been subjected to survey for socio-economic and educational information. Findings: Between groups of gender; categories such as frequency of dental brushing, awareness of parents, frequency of oral check-up, having a medical treatment and experiencing stress during the treatment, and educational level were examined via Chi square test. Among 3 groups in the list of family awareness; categories such as frequency of dental brushing, having a medical treatment, income and education level, experiencing stress during the treatment and frequency of oral check-up were compared via Chi square test. In all of the analyses significance level was measured to be 0.05. Results: The socio-economic level of families of children who have down syndrome play important role in their oral health conditions and levels.
Keywords: Ağız sağlığı; Aile; DMFT Index; DMFT İçeriği; Down sendromu; Down syndrome; Family; Oral Health; Socio-Economic; Sosyo-ekonomik Düzey